Computational evaluation of thermal management strategies in an underground mine - Sasmito, A.P. (Elsevier Ltd, 2015)
The advancement of technological development in underground mines together with increasing demands of raw materials while ore deposit in the surface depleted continuously, has led underground mines to go even deeper â up to more than 3 km nowadays. As mine delves deeper into the earth, the rock pressure and virgin rock temperature rise, which in turn have an adverse effect on the environment and thus lead to a higher cost. Typically, air ventilation itself is not sufficient to remove the heat generated, whence air conditioning system has to be added. This paper evaluates thermal management in underground mines via computational fluid dynamics approach. The three-dimensional underground cul-de-sac tunnel model together with its ventilation auxiliary and mining machinery is developed comprising conservation equations of turbulent mass, momentum and energy. Effect of ventilation flow rate, cooling load, virgin rock temperature and the heat rejection from mining machinery were evaluated with regards to the thermal comfort. Finally, this model can be used to develop an optimum or near-to-optimum ventilation and air-conditioning strategy in underground environment. Â© 2015 Elsevier Ltd